Infrastructure as Code for Security Automation and Network Infrastructure Monitoring - Wahyu Riski Aulia Putra; Agus Reza Aristiadi Nurwa; Dimas Febriyan Priambodo; Muhammad Hasbi (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2022)
The Corona Virus (COVID-19) pandemic that has spread throughout the world has created a new work culture, namely working remotely by utilizing existing technology. This has the effect of increasing crime and cyber attacks as more and more devices are connected to the internet for work. Therefore, the priority on security and monitoring of network infrastructure should be increased. The security and monitoring of this infrastructure requires an administrator in its management and configuration. One administrator can manage multiple infrastructures, making the task more difficult and time-consuming. This research implements infrastructure as code for security automation and network infrastructure monitoring including IDS, honeypot, and SIEM. Automation is done using ansible tools to create virtual machines to security configuration and monitoring of network infrastructure automatically. The results obtained are automation processes and blackbox testing is carried out and validation is carried out using a User Acceptance Test to the computer apparatus of the IT Poltek SSN Unit to prove the ease of the automation carried out. Based on the results of the UAT, a score of 154 was obtained in the Agree area with an acceptance rate of 81.05% for the implementation of infrastructure as code for the automation carried out